2017
DOI: 10.3928/01477447-20161227-02
|View full text |Cite
|
Sign up to set email alerts
|

Distal Humeral Hemiarthroplasty Versus Total Elbow Arthroplasty for Acute Distal Humeral Fractures

Abstract: For acute distal humeral fractures not amenable to open reduction and internal fixation, total elbow arthroplasty has become an established alternative. However, lifelong activity restrictions designed to prevent early mechanical failure make this a poor option for some patients. This has led to a renewed interest in distal humeral hemiarthroplasty. Using modern implants and techniques, distal humeral hemiarthroplasty has shown outcomes comparable to those of total elbow arthroplasty at short- to mid-term foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Depending on the fracture pattern, it may be impossible to make a rigid construct allowing for early full range of motion [ 15 ]. In the case of a multifragmentary fracture type with a severely comminuted articular surface, low-plane fractures, or poor bone quality caused by osteoporosis or arthritis, arthroplasty can be considered [ 15 ]. Similar to other joints, hemiarthroplasty can be considered in distal humeral fractures.…”
Section: Arthroplasty For Distal Humeral Fracturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the fracture pattern, it may be impossible to make a rigid construct allowing for early full range of motion [ 15 ]. In the case of a multifragmentary fracture type with a severely comminuted articular surface, low-plane fractures, or poor bone quality caused by osteoporosis or arthritis, arthroplasty can be considered [ 15 ]. Similar to other joints, hemiarthroplasty can be considered in distal humeral fractures.…”
Section: Arthroplasty For Distal Humeral Fracturesmentioning
confidence: 99%
“…It is mandatory to have a stable elbow joint with intact or reconstructable radial head, coronoid, and ulna in addition to intact or reconstructable collateral ligaments [ 15 17 ]. Therefore, the advantage of the reduced operative time mentioned in the literature is counteracted by the simple fact that the collateral ligaments are affected to a corresponding degree, leading to complex reconstruction with the challenge of correct tension [ 16 , 17 ]; especially since the unlinked nature of the hemiarthroplasty requires mandatory correct placement for stable kinematics [ 15 ]. Furthermore, mid- and long-term results are still missing and the impact of the implant on the ulnar and radial cartilage is unknown.…”
Section: Arthroplasty For Distal Humeral Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only one comparative systematic review of TEA versus distal humerus hemiarthroplasty, but the outcomes based on age and implant choice were not considered. 12) Thus, we aimed to analyze the clinical outcomes and complications associated with hemiarthroplasty using the single-implant system (the Latitude system) in distal humerus fractures through a systematic review of relevant literatures.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis comparing total-vs hemi arthroplasty reported a higher incidence of second ary surgery after hemi arthroplasty, mainly due to the complications of olecranon osteotomy, but there were no significant differences in functional outcome at short-to medium-term follow-up (Rangarajan et al 2017). This was not confirmed in our own register-based study that showed no significant difference in revision rate or adverse events leading to secondary surgery (Nestorson et al, unpublished data, paper IV).…”
Section: Resultsmentioning
confidence: 99%